ACEH CULTURE ON MATERNAL AND CHILD HEALTH RELATED TO INTEGRATED MANAGEMENT OF INFANT ILLNESS: A QUALITATIVE STUDY IN NORTH SUMATRA INDONESIA - Dewi Marianthi; Sri Supar Yati Soenarto; Fitri Haryanti; Yayi Suryo Prabandari (Belitung Raya Foundation, Indonesia, 2017)
Background: Maternal and infant mortality rates in Aceh province are still quite high compared to other provinces in Indonesia. In addition to disease factors, the factor that contributes to the rates is socio-cultural factor. Objective: This study aims to know and understand the view of postpartum mothers, health personnel, cadres, and the chairperson of the Aceh traditional assembly about the culture related to postpartum and newborn and integrated infant management program (MTBM) in Aceh. Methods: This was a qualitative study. Data collection was conducted from October 2016 to January 2017 on seven health cadres by focus group discussion and in-depth interviews on five postpartum mothers, one health worker, and the Aceh traditional assembly chairperson. The open-code software program was used for data analysis. Results: Three themes emerged from data: 1) The 'Madeung' Culture in postpartum mothers in Aceh has a relationship with maternal health problems, 2) 'Peucicap' and 'troen tanoh' cultures in newborns in Aceh are at risk of causing complex problems in newborns, and 3) Community-based integrated management of young infants can be implemented while maintaining Acehnese culture. Conclusion: To improve access to maternal and neonatal health services with socio-cultural issues, the community-based integrated management of young infants is considered appropriate in Aceh culture.